Development and Implementation of Charitable Pharmacy Services within a Federally-Qualified Health Center (FQHC) - Cortney M. Mospan; Katelyn M. Alexander (University of Minnesota Libraries Publishing, 2015)
Underserved patient populations often have limited access to health care services, especially medications, leading to lower quality care due to their transitional status and lack of access. To ensure access to medications for underserved patients in the Johnson City, Tennessee area, the Colleges of Nursing and Pharmacy at ETSU developed a charitable pharmacy to serve those of greatest need in hopes of improving quality of care. By establishing a community pharmacy within a FQHC, clinical community pharmacists were able to establish enhanced community pharmacy services as a part of the health-care team. This manuscript describes the development, implementation, and benefits of the community pharmacy integration within a FQHC   Type: Clinical Experience